PEWARISAN GEN KETAHANAN JAGUNG TERHADAP PENYAKIT BULAI (Peronosclerospora maydis) - Eko Hary Pudjiwati (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2020)
ABSTRACTResistance to downy mildew is influenced by the source of the inherited resistance genes or parents used in the breeding program. In assembling maize varieties resistant to downy mildew, it is important to know the number and action of genes related to downy mildew resistance. This study aims to determine the number and action of genes from three hybrid varieties, namely varieties P21, P3 and NK 33 which will be used as parents. Populations of F1 and F2 from three commercial varieties of corn hybrids were used as genetic material in this study. The results showed that resistance to P. maydis was controlled by two pairs of genes with double dominant epistasis gene action for P21 variety and recessive dominant epistasis gene action for P3 and NK33 varieties. The heritability prediction value of resistance character for the three varieties was low. The genetic progress of resistance characters in P21 and NK33 varieties was low, while P3 varieties had high genetic progress values. The P3 variety can be used as a source of resistance genes for the assembly of maize varieties that are resistant to downy mildew, and selection should be carried out in the next generation.Keywords: Corn, Downy Mildew, Inheritance, Heritability, ABSTRAKKetahanan terhadap penyakit bulai dipengaruhi oleh sumber gen yang mewariskan ketahanan atau tetua yang digunakan dalam program pemuliaan. Dalam perakitan varietas jagung tahan penyakit bulai informasi jumlah dan aksi gen terkait ketahanan penyakit bulai penting untuk diketahui. Penelitian ini bertujuan untuk mengetahui jumlah dan aksi gen dari tiga varietas hibrida yaitu varietas P21, P3 dan NK 33 yang akan digunakan sebagai tetua. Populasi F1 dan F2 dari tiga varietas hibrida jagung komersial digunakan sebagai materi genetik dalam penelitian ini. Hasil penelitian menunjukkan ketahanan terhadap P. maydis dikendalikan oleh dua pasang gen dengan aksi gen epistasis dominan ganda untuk varietas P21 dan aksi gen epistasis dominan resesif untuk varietas P3 dan NK33. Nilai duga heritabilitas karakter ketahanan untuk ketiga varietas tergolong rendah. Kemajuan genetik karakter ketahanan pada varietas P21 dan NK33 adalah rendah sedangkan varietas P3 mempunyai nilai kemajuan genetik tinggi. Varietas P3 dapat digunakan sebagai sumber gen ketahanan untuk perakitan varietas jagung yang tahan penyakit bulai, dan seleksi sebaiknya dilakukan pada generasi lanjut.Kata kunci: downy mildew, heritabilitas, jagung, pewarisan